Regularity of Functions on the Reduced Quaternion Field in Clifford Analysis. (20th March 2014) - Kim, Ji Eun; Lim, Su Jin; Shon, Kwang Ho
Abstract : We define a new hypercomplex structure of ℝ 3 and a regular function with values in that structure. From the properties of regular functions, we research the exponential function on the reduced quaternion field and represent the corresponding Cauchy-Riemann equations in hypercomplex structures of ℝ 3 .